PRESIDENTIAL THRESHOLD AS A LEGAL POLITICAL INSTRUMENT FOR SIMPLIFYING THE PARTY SYSTEM - Shaim Muhtasib Amnur; Nanik Prasetyoningsih (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
The Presidential Threshold (PT) is formally constructed as a legal instrument to strengthen the presidential system by simplifying the political party system. However, this research argues that the PT has experienced a functional shift from an instrument of stability to a mechanism of political cartelization that hinders the circulation of the national elite. This study aims to analyze the legal-political ambivalence of the PT within the context of simultaneous elections and its implications for the quality of democracy. Employing a normative-juridical method with statutory, conceptual, and case approaches, this research finds that the 20% of PT substantively creates a candidacy oligopoly that undermines popular sovereignty. The novelty of this article lies in its critical analysis of the "pseudo-stability" generated by oversized coalitions post-PT, which ultimately triggers a deadlock in parliamentary accountability. This article concludes that to preserve the integrity of simultaneous elections, the PT must be recalibrated or abolished to end the consolidation of power by party elites.